Compensatory light utilization of Phalaris arundinacea within the Phalaris arundinacea–Phragmites australis compound community. Issue 1 (1st January 2018) - Zhao, Yun; Fu, Weiguo; Li, Pingping; Xue, Ke; Wang, Yuxuan; Xing, De Ke
ABSTRACT: This study investigated the light utilization characteristics of Phalaris arundinacea within the Phalaris arundinacea - Phragmites australis compound community. The investigation was based on the response curve equation of the net photosynthetic rate-photosynthetic photon flux density (Pn-PPFD) of P. arundinacea and on the distribution of PPFD on the surface canopy of P. arundinacea within the compound community. Results showed that P. arundinacea was able to compensate for substantial reduction in available light, and utilize the weak light within the lower part of the compound community. On the one hand, the density of P. australis within the compound community determined the compensatory light utilization rate (CLUR) of P.arundinacea . On the other hand, the CLUR amplitude of P. arundinacea within the compound community with the same P. australis density was relatively small in a day. The results can help people to regulate P. arundinacea - P. australis compound communities to maintain a long-term, stable coexistence in the constructed wetlands. Abbreviations : CK – control; CLUR, compensatory light utilization rate; LER, light extinction rates; Pn, net photosynthetic rate; PPFD, photosynthetic photon flux density.